Stress Distribution on Root Dentin Analogous to Natural Teeth with Various Retentive Channels Design on the Face of the Root with Minimal or No Coronal Tooth Structure: A Finite Element Analysis - Shoeb Yakub Shaikh; Shahnawaz Mulani; Safia Shoeb Shaikh (Wolters Kluwer Medknow Publications, 2018)
Aim: the aim of this study was to evaluate post-core design on Stress distribution in maxillary central incisor with various designs retentive channels placed on the face of the root with no remaining coronal tooth structure. Materials and Methods: 3 dimensional finite element model of a maxillary central incisor was developed and seven other study modes were developed. Tooth was scanned using CBCT unit, with reverse engineering software. 3D wire mesh, with ten node tetrahedral element, developed was transferred to ANASYS software. Composite was used for post-core-crown as post endodontic restoration. Mechanical properties were assigned to each component for FEA. All the materials were assumed to be isotropic, linearly elastic, homogenous and tightly bonded. A load of 100N were applied from vertical, horizontal and lateral oblique from incisal and palatal surface respectively. Results: Analysis revealed that stresses were concentrated at the point of load application on crown(vertical(V) 14.35MPa, horizontal(H) 27.04 MPa and lateral oblique(L)13.75MPa) and depending on the post core design the stresses were homogenous evenly distributed over the root dentin, core and least over the post. There was variation in stress distribution under vertical horizontal and lateral oblique load. Conclusion: Teeth with no remaining coronal structure and by placing retentive channels on the face of the root will enable homogenous stress distribution, promote mechanical retention and stability to the post core crown post endodontic restoration.